Scott Joplin a life in ragtime - Otfinoski, Steven (New York Franklin Watts, 1995)
The story of America's most famous composer of ragtime music
American Corner
Discography: p. 131-132
Includes bibliographical references (p. 138-139) and index
11
Keywords: Joplin, Scott -- 1868-1917 -- Juvenile literature; African Americans -- Biography; Composers -- United States -- Biography -- Juvenile literature; Composers